The Application of Group Counseling Services to Minimize Academic Stress in High School Students - Chindy Asmi Abdillah; Nurhayani Nurhayani (Bisma The Journal of Counseling, 2023)
In recent years, student stress has become very visible. Academic stress is triggered by various circumstances, such as heavy workloads, lots of teaching materials or material to study, students need to excel academically, and academic demands that are reinforced by pressure from parents, school, and classmates. It is necessary to have group counseling for students to overcome these problems. The purpose of this study is to find out how effective the application of group counseling services is in minimizing academic stress in high school students. This research belongs to the type of experimental research, with a total sample of 6 high school students. Data collection in the study was carried out using questionnaires and interviews, with the research instrument being a questionnaire regarding academic stress. The data obtained in the study were then analyzed using the paired simple t-test. The results of the data analysis showed that the results of the Shapiro-Wilk normality test were pre-test 225 and post-test 099. It can be concluded that the data was > 0.05 or normally distributed. Furthermore, the paired sample t-test results showed a two-tailed significance score <0.05, meaning there was a significant difference between the initial and final variables. It indicates a significant effect on the difference in the treatment given to each variable. Based on these results, group counseling services are quite effective in minimizing academic stress on students.